1995
DOI: 10.1183/09031936.95.08010114
|View full text |Cite
|
Sign up to set email alerts
|

Time constant/volume relationship of passive expiration in mechanically ventilated ARDS patients

Abstract: T Ti im me e c co on ns st ta an nt t/ /v vo ol lu um me e r re el la at ti io on ns sh hi ip p o of f p pa as ss si iv ve e e ex xp pi ir ra at ti io on n i in n m me ec ch ha an ni ic ca al ll ly y v ve en nt ti il la at te ed d A AR RD DS S p pa at ti ie en nt ts s The mean values of τE for each volume slice did not differ significantly throughout expiration, averaging 690±218 ms (mean±SD of five slices and 12 patients). We show that the flow-dependent resistance of the endotracheal tube (RETT) is mainly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
85
2
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 21 publications
3
85
2
4
Order By: Relevance
“…GUTTMANN et al [6] observed that in patients with ARDS who were mechanically ventilated on PEEP, consecutive volume (V) portions were exhaled with nearly identical time constants (te), as indicated by a relatively constant V/flow (V9) relationship throughout expiration. This observation was attributed to to the presence of the endotracheal tube.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GUTTMANN et al [6] observed that in patients with ARDS who were mechanically ventilated on PEEP, consecutive volume (V) portions were exhaled with nearly identical time constants (te), as indicated by a relatively constant V/flow (V9) relationship throughout expiration. This observation was attributed to to the presence of the endotracheal tube.…”
mentioning
confidence: 99%
“…Indeed, taking into account the resistance of the endotracheal tube and ventilator circuit, GUTTMAN et al [6] recalculated the te of the pure respiratory system (ters) and observed a progressive increase toward the end of expiration. However, in this study [6] the ters was calculated with the assumption that the respiratory system compliance did not differ between inspiration and expiration. The possibility of hysteresis [7] renders this assumption questionable.…”
mentioning
confidence: 99%
“…16 However, there are significant differences in the time constant when it is measured at different lung volumes in subjects with lung disease. [22][23][24] Specifically, in patients with the acute respiratory distress syndrome and those with COPD, the time constant increases as expiration proceeds. 22,23 Notably, a single compartment cannot accurately describe passive expiration in intubated and paralyzed patients.…”
mentioning
confidence: 99%
“…[22][23][24] Specifically, in patients with the acute respiratory distress syndrome and those with COPD, the time constant increases as expiration proceeds. 22,23 Notably, a single compartment cannot accurately describe passive expiration in intubated and paralyzed patients. 25 However, our patients were in a stable state in the outpatient setting, as opposed to intubated under conditions of respiratory failure, 14,23 or paralysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation